PROBLEMS OF TERMINOLOGY REGULATION IN LINGUISTICS - Guzal Qurbonaliyevna Ergasheva (Bright Mind Publishing, 2025)
This article discusses the theoretical aspects of the concept of terminology, its significance in the fields of science and technology, and the formation of terms in the Uzbek language. The stages of development of psychological terminology, issues related to the regulation of terminology in Russian and Uzbek linguistics, and the role of terminological dictionaries as important scientific sources are examined. Additionally, the article analyzes problems encountered in the process of term creation, including polysemy, synonymy, and the impact of complex structured terms on linguistic economy. The emergence of new terms due to the advancement of science and technology, as well as the necessity of regulating them, is also discussed in the context of the development of psychological terminology.
Keywords: Term, terminology, psychological terms, linguistics, science and technology, term creation, synonymy, terminological dictionaries, psychology, terminology system.